2000
DOI: 10.1034/j.1600-0838.2000.010002103.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of walking on bone quality as determined by ultrasound in the elderly

Abstract: In the present study, measurements of broadband ultrasound attenuation (BUA) were used as indications of bone quality in elderly residents of an old people's home. To investigate the possibility of using number of steps walked as an indicator of the role played by exercise on bone quality, we studied the relationship between BUA and the number of steps, taken as a measure of the number of impacts against the ground placing a direct mechanical stress on the bones. The subjects were 59 healthy elderly women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…As a result, simple linear regression models were fitted to the relationships between QUS parameters and step number in the present study. Yanagimoto et al (2000) also showed a positive correlation between walking activity and QUS parameters among elderly Japanese women with a mean age of 78 years and suggested that, while not large, the accumulated small impacts from walking are a significant factor in maintaining bone quality among the elderly. It is certain that a low number of steps/day is associated with lower QUS measurements.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, simple linear regression models were fitted to the relationships between QUS parameters and step number in the present study. Yanagimoto et al (2000) also showed a positive correlation between walking activity and QUS parameters among elderly Japanese women with a mean age of 78 years and suggested that, while not large, the accumulated small impacts from walking are a significant factor in maintaining bone quality among the elderly. It is certain that a low number of steps/day is associated with lower QUS measurements.…”
Section: Discussionmentioning
confidence: 94%
“…Calcaneus measurements based on ultrasound and dual-energy X-ray absorptiometry (DXA) have been found to be useful tools for evaluating bone status [20,21]. The relationship between gait parameters and bone status has been examined using ultrasound parameters, and gait speed has been shown to be significantly associated with better bone quality in a cross-sectional study [22][23][24]. A significantly greater decline in usual gait speeds over a 2-year period in elderly women whose BMD decreased compared with those whose BMD increased has also been reported [25].…”
Section: Discussionmentioning
confidence: 99%
“…Yanagimoto et al (2000) used ultrasound densitometry as a technique for measuring bone density in determining the effect of walking on bone quality. The BUA values predict fracture risk in older women white females (Brooke-Wavell et al, 2008) and decrease with the aging process (Wehbe et al, 2003), but the higher level of BUA was noticed in people who made more steps a day, which contributed to the normal level of bone quality (Muir et al, 2013).…”
Section: Resultsmentioning
confidence: 99%